Comparison of afatinib and erlotinib combined with bevacizumab in untreated stage IIIB/IV epidermal growth factor receptor-mutated lung adenocarcinoma patients: a multicenter clinical analysis study. (July 2022) - Lee, Suey-Haur; Lin, Yu-Ching; Chiu, Li-Chung; Ju, Jia-Shiuan; Tung, Pi-Hung; Huang, Allen Chung-Cheng; Li, Shih-Hong; Fang, Yueh-Fu; Chen, Chih-Hung; Kuo, Scott Chih-Hsi; Wang, Chin-Chou; Yang, Cheng-Ta; et al.
Background: Although bevacizumab in combination with afatinib or erlotinib is an effective and safe first-line therapy for advanced epidermal growth factor receptor (EGFR)-mutated non-small-cell lung cancer (NSCLC), there are very few clinical data comparing afatinib and erlotinib combined with bevacizumab. We performed a retrospective multicenter analysis for the comparison of two combination therapies. Methods: Between May 2015 and October 2020, data of 135 stage IIIB/IV EGFR-mutated NSCLC patients receiving first-line afatinib or erlotinib combined with bevacizumab combination therapy in Linkou, Keelung, Chiayi, and Kaohsiung Chang Gung Memorial Hospitals were retrieved and retrospectively analyzed. Results: In all, 67 patients received afatinib plus bevacizumab, and 68 patients received erlotinib plus bevacizumab. Afatinib combined with bevacizumab had an objective response rate (ORR) of 82.1% and a disease control rate (DCR) of 97.0%, and the ORR and DCR were 83.8 and 95.6%, respectively, in the erlotinib combined with bevacizumab group ( p  = 0.798 and p  = 1.000). The median progression-free survival was 20.7 and 20.3 months for the afatinib plus bevacizumab group and the erlotinib plus bevacizumab group, respectively [hazard ratio (HR) = 1.02; 95% confidence interval (CI), 0.891–1.953; p  = 0.167). The overall survival was 41.9 and 51.0 months for the afatinib plus bevacizumab group and erlotinib plus bevacizumab group, respectively (HR = 1.42; 95% CI, 0.829–2.436; p  = 0.201). The secondary EGFR-T790M mutation rates after disease progression were 44% in the afatinib plus bevacizumab group and 58.8% in the erlotinib plus bevacizumab group ( p  = 0.165). Skin toxicity was the most frequent treatment-related adverse event (AE) in both treatment groups. Diarrhea, an AE, occurred significantly more frequently in the afatinib plus bevacizumab group than in the erlotinib plus bevacizumab group ( p  < 0.05). Conclusion: Afatinib combined with bevacizumab was equally as effective as erlotinib combined with bevacizumab for untreated advanced EGFR-mutated NSCLC. Prospective clinical studies that explore bevacizumab combined with afatinib or erlotinib for advanced EGFR-mutated NSCLC are warranted. Graphic abstract